2019
DOI: 10.1002/er.4690
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hybrid‐capacitor properties of ruthenium complexes

Abstract: Summary Ru complexes were successfully produced, and their structural properties were investigated using FTIR, Raman, and single crystal XRD patterns. The HOMO, LUMO, Eg, and electronic surface potential (ESP) values of the molecules were calculated by a Gaussian program. The complexes were used for producing hybrid capacitor cells as electrode materials. According to electrochemical analysis, complex 2 showed the best CV graph between −1 V and +1 V and had the highest current value and hysteresis area when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…8c) of CoMoO 4 because of a large number of active sites provided by Mo, Co and the functional groups of the organic species, as well as by spherical-shaped nanoparticles. The results of the present study is in agreement with the previous study of Altin et al, 77 where they reported the favourable electrochemistry (considerable specic capacitance) of different ruthenium complexes with four different organic compounds. They reported that the specic capacitance of ruthenium was increased due to the higher surface areas of the organic compounds.…”
Section: Supercapacitive Studiessupporting
confidence: 94%
“…8c) of CoMoO 4 because of a large number of active sites provided by Mo, Co and the functional groups of the organic species, as well as by spherical-shaped nanoparticles. The results of the present study is in agreement with the previous study of Altin et al, 77 where they reported the favourable electrochemistry (considerable specic capacitance) of different ruthenium complexes with four different organic compounds. They reported that the specic capacitance of ruthenium was increased due to the higher surface areas of the organic compounds.…”
Section: Supercapacitive Studiessupporting
confidence: 94%
“…Supercapacitors (also known as electrochemical capacitors) have gained extensive research focus in the field of energy storage due to reasonable high power density, quick charging and discharging, safe operation, and optimum working conditions . The performance of a capacitor is critically depending on its electrode . Therefore, over recent years, the development of efficient supercapacitor electrode is the focus of attention among researcher …”
Section: Introductionmentioning
confidence: 99%
“…The performance of a capacitor is critically depending on its electrode . Therefore, over recent years, the development of efficient supercapacitor electrode is the focus of attention among researcher …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bond lengths between C-N atoms are also within a certain range of value. They have an average value of 1.3544 (Å), so these bonds are weaker than the others [14]. The HOMO and LUMO energy levels of the complex and the Eg value, which is the difference between them, are given in the Table 2.…”
Section: Methodsmentioning
confidence: 99%